Follicular atresia in goat: A review - SHARMA, R K (The Indian Journal of Animal Sciences, 2014)
Follicular atresia causes extensive loss of germ cells during development, and reproductive life in female mammals. The primordial follicles are most affected during embryonic life while antral follicles out number in atresia during the active life. Atresia is a fundamental process that modulates the success of folliculogcncsis and the number of ovulations. Both morphological and functional events of follicular atresia have been discussed. The morphological (including ultra structure) and histochemical characteristics of atresia include alteration of extracellular matrix, loosening of cell to cell interactions, pycnosis, chromolysis, hyalinization, appearance of crystalloid bodies, chromophilic granules, pseudocleavage, mItochondrial aggregations, shrinking of plasma membranes, hyalinization of zona pellucid a etc. These morphological features are associated with a decline in the sensitivity of granulosa cells to gonadotrophins, degeneration by apoptosis. loss of cell to cell communication, loss of proliferative und steroidogenic activities. EndocrinologicaIly, the estradiol production declines, progesterone titre changes, FSH-binding receptors decrease, FSH-binding inhibitors increase, androgen production increases, and LS/LI ratio is altered. These changes activates some cytoplasmic or membrane bound factors that activates apoptotic genes like P53, C-myc, bcr-ab, ras, bcl-2, bel-x, bax, and anti-oxidant family of genes causing an elevation in ealpains, caspases, p53 suppressor protein, IL-2, BCL-2 and BAX that activates endonucleases leading to apoptosis. Most ofthe cellular components are endocytoised by the theca intema cells, which hypertrophy and transmutate into steroidogenieally active interstitial gland tissue. The information available on atresia in goats and sheep is discussed in relation to other mammalian species to explain the intricacies of this process and to point out the gaps for further studies.